Sb2S3-templated synthesis of sulfur-doped Sb-N-C with hierarchical architecture and high metal loading for H2O2 electrosynthesis - Minmin Yan; Zengxi Wei; Zhichao Gong; Bernt Johannessen; Gonglan Ye; Guanchao He; Jingjing Liu; Shuangliang Zhao; Chunyu Cui; Huilong Fei (Nature Communications)
Abstract Selective two-electron (2e−) oxygen reduction reaction (ORR) offers great opportunities for hydrogen peroxide (H2O2) electrosynthesis and its widespread employment depends on identifying cost-effective catalysts with high activity and selectivity. Main-group metal and nitrogen coordinated carbons (M-N-Cs) are promising but remain largely underexplored due to the low metal-atom density and the lack of understanding in the structure-property correlation. Here, we report using a nanoarchitectured Sb2S3 template to synthesize high-density (10.32 wt%) antimony (Sb) single atoms on nitrogen- and sulfur-codoped carbon nanofibers (Sb-NSCF), which exhibits both high selectivity (97.2%) and mass activity (114.9 A g−1 at 0.65 V) toward the 2e− ORR in alkaline electrolyte. Further, when evaluated with a practical flow cell, Sb-NSCF shows a high production rate of 7.46 mol gcatalyst −1 h−1 with negligible loss in activity and selectivity in a 75-h continuous electrolysis. Density functional theory calculations demonstrate that the coordination configuration and the S dopants synergistically contribute to the enhanced 2e− ORR activity and selectivity of the Sb-N4 moieties.